Case report: acute liver failure induced by paracetamol toxicity - TCACIUC, Eugen; PODUREAN, Mariana; SCHIOPU, Olga; BATRINAC, Aurel; SELIVANOV, Angela; COLOMAN, Dumitru (One Health & Risk Management, 2020)
Introduction. Paracetamol is the most commonly used drug across Western Europe and North America. There is no such trend of using Paracetamol in the Republic of Moldova, thus overdose cases are extremely rare. The mechanisms leading to overdose episodes might induce hepatotoxicity. Clinical case. This present article reports a case of acute liver failure induced by Paracetamol overdose. A 46-year-old man presented to the Medpark International Hospital. He was administered Paracetamol 1000 mg, approximately every 4 hours for 2 days, and 1000 mg twice a day for another 2 days, after an intense physical exertion, followed by muscle fever with myalgia and low-grade fever (37.4 °C) The reason for asking the medical care were pronounced fatigue, nausea, loss of appetite, night sweats, and frequent urination. Conclusion. Eventually, the case was successfully resolved due to N-acetyl-cysteine, administered according to the established treatment scheme, as well as the adjuvant therapy.